Talking international law : legal argumentation outside the courtroom - Johnstone, Ian, 1960-; Ratner, Steven R. (New York, NY : Oxford University Press, 2021)
Examining legal argumentation by states and other actors in the settings where it mostly transpires - outside of courts, 'Talking International Law' challenges the realist assumption that legal argumentation is largely inconsequential. Addressing a gap in scholarship within international law and international relations theory, this book provides a comprehensive analysis of why it occurs, how, where, and to what effect by exploring the phenomenon in a range of issue areas, from security and human rights, to the environment, trade, and intellectual property.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 15, 2021).
Keywords: International law; International law -- Political aspects; United Nations